Diversity and abundance of pollinators in different winter crops at Sher-e-Bangla Agricultural University Campus, Dhaka (Journal of Biodiversity Conservation and Bioresource Management, 2022)
The study was conducted at Sher-e-Bangla Agricultural University campus to document the diversity and abundance of pollinators of five commonly grown winter crops, viz., mustard, coriander, niger, black cumin and linseed from October 2020 to February 2021. A total number of fifteen species was identified under eleven genera, nine subfamilies, nine families and seven super families. The study revealed that honey bees, halictids, nymphalids, coccinellids, butterflies and dipterans of genera Apis, Halictus, Lasioglossum, Aglais, Coccinella, Pieris, Eurema, Musca, Syrphid and Calliphora belonging to the families Apidae, Halictidae, Nymphalidae, Coccinellidae, Pieridae, Muscidae, Syrphidae and Calliphoridae, respectively were present in the field. The species diversity was high in mustard with 15 species while it was low in linseed (5 species). The honey bees, Apis sp. and sweat bees, Halictus sp. were common pollinators of all five oilseed crops, while the housefly, Musca domestica was specific to mustard. The honey bee, Apis sp. was predominant among all the insect pollinators in five oilseed crops. The Species Richness (SR), Shannon-Weaver index (H’), Community dominance and Question of similarity indices were applied to determine the diversity and abundance of pollinators.J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(1): 33-42